"Effects of school environment, culture, parental involvement and student-teacher relationships on achievement motivation among senior secondary school students in Ibadan metropolis " (2014)
The study examined the effects of school environment, culture, parental involvement and student-teacher relationships on achievement motivation among Senior Secondary school students in Ibadan metropolis. Descriptive survey research design was adopted for this study. A multi-stage random sampling technique was employed in selecting 500 participants for the study from 15 secondary schools in Ibadan. Their ages ranged between 12 years and 20 years with the mean age of 12.4 years and the standard deviation 1.42. Pearson's Product Moment Correlation and Multiple regression analyses were used to analyze the data. The results revealed that School Culture, Parental involvement School environment and Student-teacher relationships had joint effects on the achievement motivation among Senior Secondary School students but Parental involvement is the most potent factor that has great effect on the achievement motivation among students. This research indicates that counselling psychologists, teachers and the administrators should focus on building enabling environment and develop cordial interpersonal relationship with the students. Parents need to be informed that they can contribute to the education of their children through encouragement, provision of learning materials, good relationship with teachers and active assistance among other strategies.